2011
DOI: 10.1099/ijs.0.028548-0
|View full text |Cite
|
Sign up to set email alerts
|

Methanosarcina horonobensis sp. nov., a methanogenic archaeon isolated from a deep subsurface Miocene formation

Abstract: A methanogenic organism, designated strain HB-1 T , from the domain Archaea was isolated from groundwater sampled from a subsurface Miocene formation located in Horonobe, Hokkaido, Japan. The strain grew on methanol, dimethylamine, trimethylamine, dimethylsulfide and acetate but not on monomethylamine, H 2 /CO 2 , formate, 2-propanol, 2-butanol or cyclopentanol. Cells were Gram-reaction-negative, non-motile, irregular cocci that were 1.4-2.9 mm in diameter and occurred singly or in pairs. The strain grew at 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 30 publications
(36 reference statements)
1
43
0
Order By: Relevance
“…The primary methanogenic archaea propagated on these enrichments were closely related to the cultured methanogens M. chelungpuianus and M. horonobensis (Table 3; Fig. 5), which are both methylotrophic methanogens (Shimizu et al 2011;Wu and Lai 2011). M. chelungpuianus was also the dominant archaea detected in the water samples (Fig.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The primary methanogenic archaea propagated on these enrichments were closely related to the cultured methanogens M. chelungpuianus and M. horonobensis (Table 3; Fig. 5), which are both methylotrophic methanogens (Shimizu et al 2011;Wu and Lai 2011). M. chelungpuianus was also the dominant archaea detected in the water samples (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…4). This might be because that the temperature was not optimal for the production of methane, given that the temperature range for growth was 20 to 42°C for M. horonobensis (Shimizu et al 2011), 25 to 50°C for M. congolense (Cuzin et al 2001), and 24 to 45°C for M. chelungpuianus (Wu and Lai 2011).…”
Section: Potential For Microbial Methane Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within this order, the methylotrophic methanogens 'Methanococcoides vulcani' (L' Haridon et al, 2014), Methanolobus profundi (Mochimaru et al, 2009), Methanolobus zinderi (Doerfert et al, 2009), Methanosarcina baltica (von Klein et al, 2002), Methanosarcina horonobensis (Shimizu et al, 2011) and Methermicoccus shengliensis (Cheng et al, 2007) were originally isolated from deep subsurface environments such as marine sediments, formation waters from oil and gas reservoirs, and coal beds. It has been reported that methylotrophic methanogens are predominantly detected among archaea in coal seams (Dawson et al, 2012;Guo et al, 2012;Shimizu et al, 2007;Wawrik et al, 2012) and they have been suggested to be associated with the anaerobic degradation of coal to methane (Strąpoć et al, 2010).…”
mentioning
confidence: 99%
“…This putative operon was found in all members of mazei-WC, including M. mazei C16, but excluding M. mazei WWM610 and the two closest isolates, suggesting a recent loss in this subclade. This gene set was also found in a sparsely distributed set of Methanosarcina strains, namely M. horonobensis HB1 (Shimizu et al, 2011), M. sp. Naples 100 and M. calensis Cali.…”
Section: Gene Flow Between Cladesmentioning
confidence: 91%